2019
DOI: 10.9788/tp2019.2-14
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Therapy and Virtual Reality Exposure for Public Speaking Anxiety

Abstract: Virtual reality (VR) has been shown to be eff ective in the treatment of anxiety disorders. The eff ects of a behavioral intervention procedure that included exposure to VR, diaphragmatic breathing, diff erential reinforcement, and functional analysis of behavior of participants with public speaking anxiety were investigated. The Virtua Therapy simulator with an Oculus Rift® was used for VR exposure. Six university students participated in the procedure involving the following sequence of sessions: initial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In a systematic review, Daniels et al (2020) identified 14 studies conducted from 2009 to 2019 that used VR as a tool to diminish public speaking anxiety (PSA). From these 14 studies, 7 belonged to clinical settings (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010;Lister, 2016;Lindner et al, 2018;Yuen et al, 2019;Zacarin et al, 2019). Three of the 7 clinical studies (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010) compared PSA levels before and after VR immersion and found a significant PSA reduction.…”
Section: E Ects Of Vr To Treat Public Speaking Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, Daniels et al (2020) identified 14 studies conducted from 2009 to 2019 that used VR as a tool to diminish public speaking anxiety (PSA). From these 14 studies, 7 belonged to clinical settings (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010;Lister, 2016;Lindner et al, 2018;Yuen et al, 2019;Zacarin et al, 2019). Three of the 7 clinical studies (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010) compared PSA levels before and after VR immersion and found a significant PSA reduction.…”
Section: E Ects Of Vr To Treat Public Speaking Anxietymentioning
confidence: 99%
“…Lister (2016), in a study with 98 participants that compared a VR condition to a control condition, concluded that six sessions were capable of increasing confidence of speakers and obtained positive self-statements. Two clinical studies included in the systematic review did not include control conditions, namely Yuen et al (2019) and Zacarin et al (2019). Yuen et al (2019) in two pilot studies with 11 and 15 participants each, showed that 6 weekly sessions were enough to significantly reduce PSA in a 3-month follow-up test.…”
Section: E Ects Of Vr To Treat Public Speaking Anxietymentioning
confidence: 99%
“…Multimedia Appendix 5 depicts the distribution of total participants. Most of the articles (13/34, 38%) included <10 participants [ 26 , 31 - 34 , 36 - 38 , 40 - 42 , 45 , 55 ], whereas two studies had >90 participants [ 35 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…SAD was the most studied, with 3% (9/34) of studies focusing on using VR therapy solely for patients with SAD [ 29 , 34 , 37 , 41 , 47 , 50 , 52 - 54 ]. Generalized anxiety disorder (6/34, 18%) [ 27 , 28 , 39 , 42 , 46 , 49 ] was next, followed by public speaking anxiety (4/34, 12%) [ 14 , 31 , 51 , 56 ]. The rest of the studies aimed at specific clinical conditions such as paruresis [ 40 ], exam anxiety [ 48 ], driving-related [ 38 ] or car passenger anxiety [ 30 ], disruptive behavior in the classroom [ 45 ], or social anxiety in children with autism spectrum disorder [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation